Highly saturated EDFA for gain clamping operation - Muhd-Yassin, Shahrin Zen; Harun, Sulaiman Wadi; Ahmad, Harith; Abd-Rahman, Mohd Kamil (John Wiley & Sons, 2007)
A highly saturated erbium-doped fiber amplifier (EDFA) that can be used for gain-clamping is demonstrated. This amplifier utilizes a short length of active fiber to provide a small but maximum gain and a high pump power to enhance the gain dynamic range. The gain for two simultaneous equal strength input signal channels is clamped at 19.3 dB from -34 dBm to -14 dBm with gain variation of less than 1 dB. The corresponding noise figure is obtained at 3.4 dB, which is slightly lower compared with the normal EDFA. This amplifier is expected to have a low transient power excursion since no compensating light is used inside the system.